The mitochondrial DNA D-loop diversity of Bali cattle in breeding centers. Issue 1 (April 2020) - Hikmawaty; Jakaria; Gunawan, A; Dagong, M I A; Rahim, L
Abstract: Bali cattle is one important native cattle breeds of Indonesia which are contributing to the development of livestock and devote meat production. The aim of this study was to evaluate the genetic profiles using of mtDNA D-loop method in Breeding centers Bali cattle which consist BPTU Pulukan (Bali), BPTHMT Serading (West Nusa Tenggara) and VBC Barru district (South Sulawesi). The complete D-loop sequences, 1145bp in length, 48 individual sample from three breeding centers (24 males and 24 females) were analyzed. mtDNA D-loop amplification were performed by Polymerase Chain Reaction (PCR). The Molecular data of the D-loop mtDNA sequences were aligned and analyzed with reference ( Bos indicus and Bos taurus ) from GenBank using Basic Local Alignment Search Tool (BLAST) and MEGA version 5.0 software. The analyzedsequences length of the D-loop mtDNA was performed on 410 bp. The result of the mtDNA D-loop showed that there were 84 site varation were 2 site deletion, 8 site insertion and 74 site substitution of mtDNA D-loop Bali cattle. The nucleotide sequences of Bali cattle had a common Bali cattle in BPTU to BPTHMT with genetic distance more closely than the Bali cattle of VBC. It can be concluded that D-loop mtDNA could be used as potential candidate marker to differentiate and grouping in breeding centers of Bali cattle.